2006
DOI: 10.1186/1471-2202-7-38
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic depression and short-term habituation are located in the sensory part of the mammalian startle pathway

Abstract: Background: Short-term habituation of the startle response represents an elementary form of learning in mammals. The underlying mechanism is located within the primary startle pathway, presumably at sensory synapses on giant neurons in the caudal pontine reticular nucleus (PnC). Short trains of action potentials in sensory afferent fibers induce depression of synaptic responses in PnC giant neurons, a phenomenon that has been proposed to be the cellular correlate for shortterm habituation. We address here the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…An overall sensitization is often found in the first 2–4 trials of a block of startle-eliciting stimuli, followed by a gradual decline in responses (habituation) to the remainder of presented trials (Aggernaes et al, 2010; Meincke et al, 2004). Habituation (short-term) is assumed to be caused by synaptic mechanisms intrinsic to sensory pathways (Davis et al, 1982; Leaton et al, 1985; Simons-Weidenmaier et al, 2006). Specifically, short-term habituation of startle has been proposed to be caused by activity-induced synaptic depression at the sensorimotor synapses in the pontine reticular formation, mediated by the activation of voltage- and calcium dependent large conductance potassium channels, called Maxi K, KCa1.1, or BK channels (Simons-Weidenmaier et al, 2006; Typlt et al, 2013b; Weber et al, 2002).…”
Section: Objective Measurement Of Sensory Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…An overall sensitization is often found in the first 2–4 trials of a block of startle-eliciting stimuli, followed by a gradual decline in responses (habituation) to the remainder of presented trials (Aggernaes et al, 2010; Meincke et al, 2004). Habituation (short-term) is assumed to be caused by synaptic mechanisms intrinsic to sensory pathways (Davis et al, 1982; Leaton et al, 1985; Simons-Weidenmaier et al, 2006). Specifically, short-term habituation of startle has been proposed to be caused by activity-induced synaptic depression at the sensorimotor synapses in the pontine reticular formation, mediated by the activation of voltage- and calcium dependent large conductance potassium channels, called Maxi K, KCa1.1, or BK channels (Simons-Weidenmaier et al, 2006; Typlt et al, 2013b; Weber et al, 2002).…”
Section: Objective Measurement Of Sensory Processingmentioning
confidence: 99%
“…Habituation (short-term) is assumed to be caused by synaptic mechanisms intrinsic to sensory pathways (Davis et al, 1982; Leaton et al, 1985; Simons-Weidenmaier et al, 2006). Specifically, short-term habituation of startle has been proposed to be caused by activity-induced synaptic depression at the sensorimotor synapses in the pontine reticular formation, mediated by the activation of voltage- and calcium dependent large conductance potassium channels, called Maxi K, KCa1.1, or BK channels (Simons-Weidenmaier et al, 2006; Typlt et al, 2013b; Weber et al, 2002). Sensitization and long-term habituation are caused through an extrinsic modulation of the startle pathway by structures including the pedunculopontine tegmentum, the cerebellar vermis, the amygdala and the bed nucleus of the stria terminalis (Davis et al, 1997; Gonzalez-Lima et al, 1989; Koch, 1999; Leaton and Supple, 1986, 1991).…”
Section: Objective Measurement Of Sensory Processingmentioning
confidence: 99%
“…Interestingly, Castelluci et al (1978) analyzed the habituation behavior in Aplysia and showed that both, short-and long-term habituation produce a profound depression in the efficacy of synaptic transmission. More recently, Simons-Weidenmaier et al (2006) proposed that the habituation of the startle response in rats is mediated by synaptic depression of the sensory pathway. In sum, it is widely accepted that habituation is mediated by a synaptic depression of the neuronal circuitry.…”
mentioning
confidence: 99%
“…This reflex is a protective response to a sudden acoustic, tactile or vestibular stimulus and is initiated by mechanoreceptors that detect mechanical forces applied to the body 11 . Stimulation of these sensory receptors elicits the activation of small clusters of giant neurons located in the pontine reticular nucleus (PnC) that project directly and indirectly to motor neurons in the facial motor nucleus and the spinal cord, leading to a fast activation of a number of facial and peripheral muscles, as well as a positive autonomic activation 1318 . The hypothesis underlying this proof-of-concept study is that bursts of kinesthetic stimulation delivered during the early phase of apneas or hypopneas may elicit a cotrolled startle response that can activate sub-cortical centers controlling upper airways muscles and the autonomic nervous system, stopping respiratory events without generating a cortical arousal.…”
Section: Introductionmentioning
confidence: 99%